KEPATUHAN PAJAK RESTORAN : PENGARUH KESADARAN, PENGETAHUAN, SIKAP, SANKSI DAN AKUNTABILITAS PELAYANAN PUBLIK: RESTAURANT TAX COMPLIANCE: EFFECT OF AWARENESS, KNOWLEDGE, ATTITUDE, SANCTIONS, AND PUBLIC SERVICE ACCOUNTABILITY - Azura, Ria; Yusralaini, Yusralaini; Odiatma, Fajar (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
This study is designed to test and prove whether taxpayer awareness, tax knowledge, taxpayer attitudes, tax penalties, and public service accountability have a significant impact on taxpayer compliance of restaurants in the city of Pekanbaru. This research is survey research. The population in this study are restaurant taxpayers registered with the Regional Revenue Agency Office in Pekanbaru City. Samples were taken from up to 100 respondents. The sampling technique used was targeted sampling. The data collection technique is a questionnaire. The statistical tool used is multiple linear regression. The results show that taxpayer awareness, tax knowledge, taxpayer attitudes, and tax penalties affect restaurant taxpayer compliance, and public service accountability significantly affects restaurant taxpayer compliance in Pekanbaru City.